2016
DOI: 10.17221/731/2015-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cultivar, flesh colour, locality and year on carotenoid content in potato tubers

Abstract: In this study, twelve cultivars of potato with different flesh colour (yellow, purple and red) were cultivated in 2012 and 2013 in two trial localities in the Czech Republic and evaluated for the main individual carotenoids. The content of total carotenoids (TC) in analysed cultivars ranged in 1.1-12.2 mg/kg in dry matter (DM) and was influenced by genotype cultivar, locality and year. Cv. Agria (yellow flesh) reached 1.8 to 11.8 times higher levels of TC compared with cultivars of coloured flesh. Locality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…A higher proportion of lutein in white fleshed potatoes was observed by Haynes et al (2010). This was also found in cultivars in which tuber flesh color is determined by anthocyanin pigments (Hamouz et al 2016;Hejtmánková et al 2013). Brown et al (2008) found the lutein as a main carotenoid in potatoes.…”
Section: Concentration Of Carotenoidsmentioning
confidence: 59%
See 2 more Smart Citations
“…A higher proportion of lutein in white fleshed potatoes was observed by Haynes et al (2010). This was also found in cultivars in which tuber flesh color is determined by anthocyanin pigments (Hamouz et al 2016;Hejtmánková et al 2013). Brown et al (2008) found the lutein as a main carotenoid in potatoes.…”
Section: Concentration Of Carotenoidsmentioning
confidence: 59%
“…The effects of environmental factors on the accumulation of carotenoids in potato tubers were rarely evaluated. Usually, authors of these studies found that carotenoids concentration depend on genotype and various environmental factors (Haynes et al 2010;Hejtmánková et al 2013;Hamouz et al 2016;Kotíková et al 2007;Othman 2009;Payyavula et al 2012;Reddivari et al 2007;Tatarowska et al 2014), but sometimes an influence of environment was not found (Brown et al 2008). In the presented study, the environmental effects were slightly higher (in the case of TC) or clearly lowered (in the case of lutein) as compared to the effect of genotype.…”
Section: Influence Of Environmental Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In banana, a single assay suggests that mature‐green Cavendish banana exhibits a higher total phenolic content when harvested in the dry season rather than in the wet one (Bruno Bonnet et al., ). Moreover, in potato, total carotenoids increased by 10% in a warmer and drier year, as compared to a colder year (Hamouz, Pazderu, Lachman, Cepl, & Kotikova, ).…”
Section: Influence Of Extrinsic Factorsmentioning
confidence: 99%
“…The content of carotenoids is affected by cultivar and locality. Hamouz et al (2016) reported that the content of total carotenoids in analysed cultivars ranged in 1.10-12.2 mg/kg DW and was influenced by genotype cultivar, locality and year. Breithaupt and Bamedi (2002) suggested that the total concentration of carotenoids in potatoes could be used as a tool to differentiate between white-or yellow-fleshed cultivars.…”
mentioning
confidence: 99%